Increasing PhD student self-awareness and self-confidence through strengths-based professional development - Ferguson, Connor L.; Lockman, Julie A. (Frontiers in Education, 2024)
Strengths-based programs have emerged as asset-based approaches to professional development that promote positive student engagement and success. This paper shares the outcomes of a strengths-based professional development program provided to biomedical and health sciences graduate doctoral students within an academic health center. Program outcomes and changes in participants’ perceived confidence when identifying and applying their strengths in different contexts were evaluated through a mixed methods design that included a Likert-based survey and thematic analysis of qualitative responses. Findings strongly suggest that most participants lacked the self-confidence and/or self-awareness to recognize their own strengths prior to the program. Themes that emerged upon implementation of the program point to the following outcomes: participants gained an increased understanding of their strengths, confidence that the knowledge gained about their strengths would help them learn more effectively in laboratory settings, an increased belief that they possess natural talents and skills that make them good scientists and strong members of their research team, and confidence that applying their strengths will help them to overcome both personal and professional challenges. This program shows promise to strengthen graduate student self-awareness and self-confidence. Further studies are needed to understand and measure how asset-based programs such as this can impact graduate student resilience, science identity, and overall student success.